A promotion of stability for temporal compression based on SBS in an interferometric scheme. Issue 17 (24th September 2016) - Wang, Yulei; Liu, Zhaohong; Yuan, Hang; Bai, Zhenxu; Wang, Hongli; Zhu, Xuehua; Liu, Rui; Li, Sensen; Chen, Yi; Wang, Yirui; Cui, Can; Zhang, Hengkang; et al.
Abstract: An approach that introducing a standing wave into focal area to stabilize the output energy and duration of stimulated Brillouin scattering (SBS) compression is presented. An interferometric scheme filled with FC-770 is used to improve the stability of both output energy and duration two times compared with an equivalent conventional SBS compressor. Moreover, the interferometric scheme shows a promotion for the performance of SBS compression.